BOTANICALS AS PROSPECTIVE AGENTS AGAINST SARS-COV-2 VIRUS - V. DUSHENKOV; A. DUSHENKOV (Avicenna Tajik State Medical University, 2022)
Objective: To assess the potential role of botanicals as therapeutic agents against the SARS-CoV-2 virus. Methods: This narrative review examined the potential role of botanicals as therapeutic agents against the SARS-CoV-2 virus based on the references limited to the English language and published up to February 2022 and retrieved from common academic search engines using multiple keywords and their combinations. The scientific names of plant species were confirmed using World Flora Online (https://wfoplantlist.org/). Results: The role of botanicals in targeting druggable points in the virus replication cycle has been evaluated. This includes the potential role of phytochemicals and medicinal plant concoctions in preventing the virus from entering the cell. Furthermore, the agents have been shown to hinder the attachment of S protein to angiotensin-converting enzyme 2, block RNA-dependent RNA Polymerase, inhibit 3-chymotrypsin like protease, main protease, neuraminidase, and other enzymes involved in virus replication. Special attention was played to the role of botanicals as immunomodulators and adaptogens. Conclusion: Botanicals have a high potential as prospective agents in managing viral diseases. Botanicals' mode of action(s) may be based on their direct interference with the virus's ability to enter human cells, virus replication, or their activation of the immune-modulatory and anti-inflammatory responses. In addition, the adjuvant treatments with botanicals have the potential to result in advances in symptom resolution, decrease disease burden and shorten disease duration.